A Comparative Study of Cross Finger Flap with Thenar Flap for Finger Tip Reconstruction - Kumar Pradhan, Suresh; Man Rai, Shankar; Dahal, Peeyush (Annapurna Journal of Health Sciences, 2023)
Introduction: Fingertip injuries are common hand injuries ranging from simple laceration to larger defects with amputations. Different methods are used to reconstruct the affected finger. Cross finger flaps and thenar flaps are commonly used but it is difficult to select among these two flaps to reconstruct the finger in our settings. Method: This is a time-bound prospective comparative study conducted in 14 months duration. The aesthetic (sensibility, appearance and function as subjective assessment) and functional outcomes (2 point discrimination and range of motion) were measured. Data were analyzed using SPSS version 21. Overall significance level was maintained at ‘p’ value < 0.05. Results: There was female predisposition with average age of 34.66 years. The common mode of injury was crush injury with right hand most commonly involved hand and middle finger being commonly injured digit. On subjective assessment, the difference on rating scale on sensibility, function and appearance was not statistically significant among two groups. There were statistical significant differences in mean of static and moving 2 point discrimination among thenar flap and cross finger flap. . The mean active range of motion at three types of joint (MP, PIP, DIP) of finger were 97.660, 82.660 and 38.660 in thenar group and 88.330, 78.660 and 33.660 in cross finger group respectively which were not statistically significant. Conclusion: Our study does not find any precise characteristics for the selection of thenar and cross finger flap based on aesthetic and functional outcomes in reconstruction of fingertip injury.